TATA KELOLA PERUSAHAAN DALAM KINERJA KEUANGAN MELALUI AGENCY COST - Ashari Sofyaun; Asrid Juniar; Rini Rahmawati (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Darma Agung (LPPM_UDA), 2022)
Financial performance in the perspective of governance at the cost of mediating institutions is the research objective. The research was conducted during the period 2013-2021 in state-owned companies that went public with a purposive sampling approach. Managerial ownership, leverage and board size as a representation of corporate governance. In measuring financial capacity, ROA and Tobins'q indicators are used. As a data analysis technique, SEM-PLS multivariate analysis was used. Firm value is significantly affected by leverage, agency costs and return on assets. Leverage and agency costs Significant impact on assets. leverage and board size have a significant impact on agency costs. Leverage and board size were successfully mediated by agency costs in influencing Tobin's q and ROA.